Perceptions of the government's infant feeding guideline of medical representatives of multi-national milk companies - Ramos, Rhoda Joy F.
The infant feeding guideline in the government's 2000 Nutritional Guidelines for Filipinos (NGF) states: "Breast-feed infants exclusively up to 6 months, and then, give appropriate foods while continuing breastfeeding". This study explored the perceptions of medical representatives on the said guideline, as a whole and on each component part- exclusive breastfeeding for the first six months and appropriateness of complementary foods, in particular sugar and fats/oil. Three focus group discussions were conducted among 22 medical representatives from two multi-national milk companies in Metro Manila. The participants were all college graduates, 20-39 years of age, had worked as medical representatives for at lest six months and had undergone nutrition training in their respective companies. The participants were not aware of the guideline. After it was presented to them, they did not recognize it as composed of two connected parts. They also failed to see the first part as referring to exclusive breastfeeding, not simply breastfeeding. Their perception of breastfeeding was different from the technical definition of the government and international experts; they were strongly against exclusion of water during the first six months of infancy. As with findings from previous studies, economic and safety factors were the most cited benefits of exclusive breastfeeding; with some having the opinion that the recommendation is only for poor mothers who cannot afford to buy infant formula. The most common perceived barriers to exclusive breastfeeding were milk insufficiency and mother's work. Perceived barriers to exclusive breastfeeding were so strong that the participants were unwilling to practice or support it. The participants considered introducing solid foods at six months to be too late. Their basis for considering certain foods appropriate for infants was consistency, not nutritional quality. With their knowledge of some aspects of food composition and food-disease connection, they perceived addition of sugar, fats and oil in the infant's diet to be inappropriate, in fact, even dangerous to the health of infants. The infant feeding guideline was neither simple nor easy to understand, as claimed by government authorities who formulated it. In fact, the recommendation on exclusive breastfeeding and complementary feeding were poorly understood and were found unacceptable by the medical representatives. It is important that the guideline be monitored and evaluated in terms of how its potential users understand and accept it.